Zirconia toughening of mullite–zirconia–zircon composites obtained by direct sintering - Rendtorff Birrer, Nicolás Maximiliano (2010)
Although multi-phase ceramic materials were always used, nowadays composite materials have an important industrial and technological role, because they enlarge the design capability of the manufacturer in properties and behaviors. Some mullite–zirconia–zircon composites were recently processed and characterized which presented satisfactory properties for structural applications under severe chemical and thermomechanical conditions. The objective of the present work is to study the influence of the starting composition in the mechanical and fracture properties of mullite–zirconia–zircon composites, with different microstructures, obtained by direct sintering of binary mixtures of electrofused mullite–zirconia (MZ) and micronized zircon. The materials were consolidated by slip casting of concentrated aqueous suspensions in plaster molds from a wide range of powder compositions (between 15–85 wt% and 85–15 wt% of the two raw materials used). Flexural strength (σf), dynamic elastic modulus (E), toughness (KIC) and fracture surface energy (γNBT) were evaluated. The results were explained by microstructure and the XRD-Rietveld analysis. At low proportion, the zircon was thermally dissociated. The ZrO2 was a product of this reaction and also influenced the mechanical and fracture properties of these materials through several combined mechanisms, principally as a result of the development of microcracks due to the volume change of the zirconia grains caused by the martensitic transformation during the cooling of these composites from sintering temperature. Composites prepared with higher MZ in the starting powders showed a higher fracture toughness and initiation energy. Microstructure consisting of mullite as a continuous predominant phase in which zircon and zirconia grains were distributed showed better mechanical and fracture properties.